"The armor phenomenon" in obese patients with penetrating thoracoabdominal injuries: A systematic review and meta-analysis. Issue 3 (21st September 2022) - Chen, Andy Ze Lin; Lee, Tae Hwan; Hsu, Jeremy; Pang, Tony
Abstract : MYTH BUSTED: Fat does not truly protect one from stabbing injuries. In fact, obesity is linked to higher rates of death and complications following stabbings and shootings. #trauma #obesity #surgery. Abstract : BACKGROUND: Obesity represents a growing global health threat, which generally portends increased morbidity and mortality in the context of traumatic injuries. We hypothesized that there may exist a protective effect related to increased weight and truncal girth provided for obese patients in penetrating torso injuries, although this may not exert a significant positive impact overall upon clinical outcomes. METHODS: A comprehensive review of the literature was conducted across five databases up to March 2021 (Medline, Pubmed, Embase, Web of Science and the Cochrane library) to examine the effect of obesity on penetrating thoracoabdominal injuries. The primary outcome was to determine the rate of nonsignificant injury and injury patterns. Secondary outcomes examined were lengths of stay, complications, and mortality. Comparisons were drawn by meta-analysis. The study protocol was registered with PROSPERO under CRD42020216277. RESULTS: There were 2, 952 publications assessed with 12 meeting the inclusion criteria for review. Nine studies were included for quantitative analysis, including 5, 013 patients sustaining penetrating thoracoabdominal injuries, of which 29.6% were obese. Obese patients that sustained stab injuries underwent more nontherapeutic operations. Obese patients that sustained gunshot injuries had longer intensive care and total hospital length of stay. Obese patients suffered more respiratory complications and were at an increased risk of death during their admission. CONCLUSION: The "armor phenomenon" does not truly protect obese patients, a population that experiences increased morbidity and mortality following penetrating thoracoabdominal injuries. LEVEL OF EVIDENCE: Systematic Review and Meta-Analysis; Level IV. Abstract :